Highly efficient single‐unit white OLED device with emission from both singlet and triplet excitons. Issue 8 (19th March 2015) - Ishisone, Takahiro; Seo, Satoshi; Nonaka, Yusuke; Kawata, Takuya; Ohsawa, Nobuharu
Abstract: We succeeded in developing a single‐unit hybrid organic light‐emitting diode (OLED) device with efficient light emission from both a phosphorescent layer and a fluorescent layer. The single‐unit hybrid OLED achieved a power efficiency higher than that of a two‐unit hybrid tandem OLED with phosphorescent and fluorescent layers. Abstract : We have developed a novel single‐unit hybrid organic light‐emitting diode device in which exciplex‐triplet energy transfer is applied to a phosphorescent layer and triplet‐triplet annihilation is applied to a fluorescent layer. This device achieved an excellent color rendering index of 87 and high‐power efficiency of 84 lm/W at 1000 cd/m2. In addition, the lifetime (LT70 ) of the device was estimated to be 180 000 h at 1000 cd/m2, which is enough for lighting applications.